Bach2 repression mediates Th17 cell induced inflammation and associates with clinical features of advanced disease in chronic pancreatitis. Issue 2 (March 2018) - Sasikala, M; Ravikanth, VV; Murali Manohar, K; Deshpande, Neha; Singh, Sandhya; Pavan Kumar, P; Talukdar, R; Ghosh, Sudip; Aslam, Mohsin; Rao, GV; Pradeep, R; Reddy, D Nageshwar
Objectives: Altered immune homeostasis and involvement of T cells has been reported in chronic pancreatitis (CP). We evaluated the role of Bach2 (BTB and CNC homology basic leucine zipper transcription factor 2), a key regulator of immune homeostasis in the chronicity of CP. Methods: Expression of Bach2 and T-cell transcription factors, enumeration of BACH2+/CD4+ T-lymphocytes were performed by qRT-PCR and flow cytometry respectively. Bach2 silenced human CD4+ T-lymphocytes were exposed to CP tissue extract to assess T-cell lineage commitment. Aryl hydrocarbon receptor ( Ahr ) and Deubiquitinase enzyme A (DUBA/ OTUD5gene ) were evaluated as markers of persistent Th17 cell differentiation. Bach2 gene (exons) was sequenced to identify risk variants and functionally validated. Results: Decrease in Bach2 ( p < 0 . 0001) and increase ( p < 0 . 001) in TBX21, RORC, Ahr, PRDM1, IL23R mRNA were noted in pancreatic tissues, while BACH2+/CD4+ T-lymphocytes were decreased ( p < 0.01) in circulation and tissues. Exposure of Bach2 silenced CD4+ T-lymphocytes to CP tissue extract showed increased Ahr, decreased OTUD5, and enhanced Th17 cell differentiation. Sequencing of Bach2 gene revealed association of novel variant (rs9111 in 5′-UTR) with advanced disease and luciferase assay confirmed its role in Bach2 repression. Conclusion: Bach2 repression mediates Th17 cell induced inflammation and rs9111-TT in individuals with primary genetic susceptibility to CP is associated with clinical features of advanced disease.